Examination of Possibilities for Increasing Sugar Content - Varga, Lajos (Acta Agraria Debreceniensis, 2003)
The result of sugar beet production is highly effected by the quality and the yield. Those agricultural techniques are very important which can be applied at low cost to improve these parameters. Such an opportunity is to increase sugar yield by foliar fertilization with nutrients and by treatment with bioactive fungicides. In my small block trial I examined the effect of the magnesium and strobilurin active ingredients in different combinations and at different application times on the quality and the yield of sugar beet. I found that there was a signifficant increase in sugar content on that blocks which were treated with a bioactive ingredient combined with magnesium in the middle of July and on those which were sprayed with bioactive ingredient in August.